Nose-to-brain delivery of self-assembled curcumin-lactoferrin nanoparticles: Characterization, neuroprotective effect and in vivo pharmacokinetic study - Li, Linghui; Tan, Liwei; Zhang, Qian; Cheng, Yushan; Liu, Yayuan; Li, Rui; Hou, Shuguang (Frontiers in Bioengineering and Biotechnology, 2023)
Curcumin (CUR) is a natural polyphenol extract with significant antioxidant and anti-inflammatory effects, which indicates its great potential for neuroprotection. Lactoferrin (LF), a commonly used oral carrier and targeting ligand, has not been reported as a multifunctional nanocarrier for nose-to-brain delivery. This study aims to develop a nose-to-brain delivery system of curcumin-lactoferrin nanoparticles (CUR-LF NPs) and to further evaluate the neuroprotective effects in vitro and brain accumulation in vivo. Herein, CUR-LF NPs were prepared by the desolvation method with a particle size of 84.8 ± 6.5 nm and a zeta potential of +22.8 ± 4.3 mV. The permeability coefficient of CUR-LF NPs (4.36 ± 0.79 × 10−6 cm/s) was 50 times higher than that of CUR suspension (0.09 ± 0.04 × 10−6 cm/s) on MDCK monolayer, indicating that the nanoparticles could improve the absorption efficiency of CUR in the nasal cavity. Moreover, CUR-LF NPs showed excellent protection against Aβ25-35-induced nerve damage in PC12 cells. In vivo pharmacokinetic studies showed that the brain-targeting efficiency of CUR-LF NPs via IN administration was 248.1%, and the nose-to-brain direct transport percentage was 59.7%. Collectively, nose-to-brain delivery of CUR-LF NPs is capable of achieving superior brain enrichment and potential neuroprotective effects.